Consolidated bioprocessing of lactose into lactic acid and ethanol using non-engineered cell factories. (February 2022) - Panagopoulos, Vassilios; Boura, Konstantina; Dima, Agapi; Karabagias, Ioannis K.; Bosnea, Loulouda; Nigam, Poonam S.; Kanellaki, Maria; Koutinas, Athanasios A.
Graphical abstract: Highlights: Provide a cell factory of Saccharomyces cerevisiae without genetic modification. Consolidated bioprocesses in one batch (CBP) for lactose fermentation. Achieving the 96% of the theoretical ethanol yield. Achieving the 89% of the theoretical lactic acid yield. Promising results for the whey exploitation. Abstract: The aim of this study is the consolidated bioprocessing of lactose into lactic acid and ethanol using non-engineered Cell Factories (CFs). Therefore, two different types of composite biocatalysts (CF1-CF2) based on Saccharomyces cerevisiae with immobilized microorganism or enzyme on starch gel (SG) were prepared for 5% w/v lactose fermentation. In CF1, S. cerevisiae was covered with SG containing Lactobacillus casei, Lactobacillus bulgaricus, Kluyveromyces marxianus CF1a-c. S. cerevisiae/ SG - β-galactosidase (CF1d) was also used for simultaneous saccharification and fermentation (SSF) of lactose. In CF2, S. cerevisiae immobilized on tubular cellulose (TC) was covered with SG containing the aforementioned microorganisms (CF2a-c). The wet CF1d resulted in 96% of the theoretical ethanol yield while the wet CF1b and freeze-dried CF2b resulted in 89% of the theoretical lactic acid yield. The repeated batches using the CF2a-c exhibited better results than using CF1a-c. Subsequently, the freeze-dried CF2 as preservative and more manageable were verified for future exploitation of whey.